Black Barbadians in Canada: A Growing Migration, 1966–1990 - Quintyne, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
Canada is considered a multiracial nation. An important part of its multiracial composition traces back to the 1960s and early 1970s, with changes to immigration regulations and the implementation of its multicultural policy. Interwoven in this multiracial mosaic called Canada is the Black person, whose presence in Canada dates back to the seventeenth century. Yet Black people in Canada are usually treated as newcomers. Among them were Black Barbadians. They came for various reasons, particularly the restructuring of Canada’s immigration policy in the 1960s. Prior to the 1960s, Canada’s immigration policy was restrictive, especially toward Black and Asian people, with Black people seldom meeting the criteria to gain entry to the country. This paper explores two key reasons that motivated Black Barbadians to migrate to Canada in increased numbers from the mid-1960s to 1990. Specifically, it argues that fundamental changes in the 1960s to Canada’s discriminatory immigration policies and the Seasonal Agricultural Workers Program were integral in motivating Black Barbadians to choose to migrate.